Effect of chromium content on the three-body-type abrasive wear behavior of multi-alloyed white cast iron - Opapaiboon, Jatupon; Supradist Na Ayudhaya, Mawin; Sricharoenchai, Prasonk; Inthidech, Sudsakorn; Matsubara, Yasuhiro (Journal of Metals, Materials and Minerals, 2019)
The effect of Cr content on three-body-type abrasive wear behavior of multi-alloyed white cast iron was investigated. Multi-alloyed white cast irons were prepared with varying Cr content from 3-9 mass% under basic alloy composition. Annealed specimens were hardened from 1323 and 1373K austenitizing and tempered at three levels of temperatures which were at maximum hardness (HTmax), lower and higher than that at HTmax (L-HTmax and H-HTmax). A rubber wheel wear tester was used to evaluate the abrasive wear resistance. The hardness and volume fraction of the retained austenite (VÎ³) varied depending on Cr content and heat treatment condition. The linear relation between wear loss and wear distance was obtained in all specimens. In each heat treatment condition, the wear rate (Rw) value decreased to 6 mass%Cr, and then, increased gradually as Cr content increased. As-hardened specimens showed higher wear resistance than tempered specimens did. In tempered state, the lowest Rw was obtained in HTmax specimen and the highest in L-HTmax or H-HTmax specimens. The Rw lowered greatly as the macro-hardness rose to 830 HV30, and after that it decreased continuously as the hardness increased. Moreover, Rw scattered broadly at VÎ³ lower than 5%, and then, decreased gradually as VÎ³ rose.